PERTANGGUNGJAWABAN PRIBADI DIREKSI PADA PERSEROAN TERBATAS YANG PAILIT - Setianto, Verina Yuwono (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2017)
In principle, the Board of Directors shall not be personally liable for acts committed for and on behalf of the company based on the authority it possesses. This is because the actions of the Board of Directors are viewed as the actions of the Company which is the subject of independent law so that the company is responsible for the actions of the company itself which in this case is represented by the Board of Directors. Due to the limited liability which is characteristic of the Limited Company, the Limited Company must be responsible for the engagement made between the Company and a third party. The principle of limited liability is what is often used by many people to choose the form of legal entity Limited Company, because by using the construction of the Limited Company, it can minimize the risk of losses that may arise. However, in some cases the board of directors may also be held personally liable in the event of bankruptcy of Limited Company when the bankruptcy of the Limited Company is caused by errors / omissions made by the Board of Directors in conducting the task of Limited company so that the law will be imposed personal responsibility to the Director who is guilty / negligent.